he Use of Code-Mixing in Naura Ayu's Endorsement Videos on SunSilk Multivitamin Hair Perfume - Ufik Dwi Agustin (Fakultas Ilmu Budaya, 2025)
The pervasive usage of code-mixing on social media, particularly in public figures' promotional content, served as the starting point for this research. Naura Ayu, for instance, frequently employs code-mixing in her Instagram promotion videos. Studying this occurrence is intriguing since it can reveal communication tactics used in conveying messages to reach audiences. This research attempts to determine the different forms of code-mixing that are employed and examine the motivations for their use. Since the data gathered in this research is non-numerical, this research is categorized as qualitative research. The data were obtained from two endorsement videos of Naura Ayu in which code-mixing phenomenon occurs. Muysken's (2000) types of code-mixing theory and Suandi's (2014) causal factors of code-mixing theory, which comprises thirteen categories, were used to examine the data. The research's findings show that insertion is the most common sort of codemixing. There are also numerous justifications for code-mixing to occur, such as mode of conversation, topic of conversation, discussion setting, speaker's personality, and the use of more popular terms. This indicates that code-mixing uttered by her is influenced by the communication needs which is associated with the message content and her target audience. As a celebrity and Gen Z, she employed code-mixing to support a target-market-appropriate communication style and to establish closeness between herself and her followers. In the context of digital promotion, language form is influenced by both linguistic and social aspects.
upload by Teddy_02/02/2026
Keywords: Code-Mixing; Endorsement Videos